ANALYZING THE SHOT PREFERENCES IN SINGLE-MEN’ AND SINGLE -WOMEN’S MATCHES OF BADMINTON CHAMPIONSHIPS AND THE EFFECTS ON MATCH SCORES - Tekdemir, Ramazan; Kizilet Bozdogan, Tuba; Kizilet, Ali (Acta Scientiae et Intellectus, 2024)
The present study aims to examine each rally played by single-man and single-woman players in Olympic, European, and World championships at finals and semi-finals from the aspect of shot preferences, as well as examining the effects of those shot preferences on the match scores. The study group consists of 20 athletes that played in final and semi-final singles matches. In the present study, the match videos uploaded to Kinovea program were played by reducing to the 3-30% of the normal play speed, and the shots preferred by the athletes were accurately recorded. In order to evaluate the effects of shooting technics on the match score, the independent sample t-Test was employed (Mann-Whitney Test) (p<0.05). It was determined that the shots mostly preferred by the male athletes were lop and net drop, whereas the least preferred type was found to be the drive. Among the female athletes, the most preferred shooting technics were clear and lop, whereas the least preferred shot was drive. Given the results related with the effects of shots preferred in scores won on the match scores, it was determined in independent t-Test results that there were statistically significant positive differences between match score and drop (r=0.03) and lop (r=0.02) among the shots received and lop (r=0.045) from the defense among the shots, from which the score was made (p<0.05). In conclusion, it was determined that, when compared to the male athletes, the female athletes kept the ball in the match longer. It can be said that the badminton athletes play a defense-oriented match and thus they win the matches by pressing the opponents into failure.